2020
DOI: 10.3390/ani10010169
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Fermentation and Fatty Acid Composition of Milk of Mid Lactating Dairy Cows Grazing Chicory and Ryegrass

Abstract: The goals of the current study were to investigate the effects of including chicory (Cichorium intybus L.) into the traditional feeding regime of ryegrass/white clover (Lolium perenne L./Trifolium repens L.), and time of its allocation on milk production, rumen fermentation, and FA composition of milk and rumen digesta of dairy cows. Nine groups of four cows were allocated one of three replicated feeding regimes: (1) ryegrass/white clover only (RGWC), (2) ryegrass/white clover + morning allocation of chicory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
(65 reference statements)
1
12
1
Order By: Relevance
“…The hypothesis that the COMP forage treatment would have improved forage nutritive value compared with the SIMP treatment would agree with the IVTDMD48 and ADF values observed in this experiment. Although birdsfoot trefoil did not establish as desired, the high forage chicory concentration in 2018 and clover content in following years may explain the difference observed here ( Labreveux et al, 2004 ; Soder et al, 2006 ; Mangwe et al, 2020 ). Additionally, both grazing treatments were dominated by grass species in 2020 could explain the convergence between the two treatments in nutritive value that year, particularly in IVTDMD48 in COMP pastures ( Deak et al, 2007 ; Sanderson et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The hypothesis that the COMP forage treatment would have improved forage nutritive value compared with the SIMP treatment would agree with the IVTDMD48 and ADF values observed in this experiment. Although birdsfoot trefoil did not establish as desired, the high forage chicory concentration in 2018 and clover content in following years may explain the difference observed here ( Labreveux et al, 2004 ; Soder et al, 2006 ; Mangwe et al, 2020 ). Additionally, both grazing treatments were dominated by grass species in 2020 could explain the convergence between the two treatments in nutritive value that year, particularly in IVTDMD48 in COMP pastures ( Deak et al, 2007 ; Sanderson et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 51%
“…Additionally, Aitchison et al (1986) found that clover hay had significantly faster rates of digestion of DM and NDF compared with grass hay, and that rumen pool sizes were lower for sheep offered clover hay. The 50% inclusion of chicory in year 1 may have had similar impacts on rumen fermentation as clover ( Waghorn et al, 2002 ; Hristov et al, 2013 ; Mangwe et al, 2020 ). Inclusion of forage chicory has inconsistent results on enteric CH 4 ( Sun et al, 2011 ; Williams et al, 2016 ) and most studies have not found it to be a viable option for CH 4 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Chicory (cv. Choice) fed to dairy cows has shown to increase water intake and reduce urinary nitrogen concentration [8] in addition to supporting greater milk production [9,10] and enhance milk fatty acids profile [11,12]. However, the adoption of alternative forages in different grazing systems requires confidence in the response to management decisions and needs to identify risks to production in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, during biohydrogenation trans fatty acids are formed with a preference for the double bond in position 11 with vaccenic acid (18:1 trans-11) being the major product. The maximum content of rTFA in ruminant fat and milk reaches about 6% (Mangwe et al 2020). Unlike elaidic acid, vaccenic acid is efficiently converted by desaturases from a wide range of organisms to rumenic acid, the cis-9-trans-11 isomer of conjugated linoleic acid.…”
Section: Introductionmentioning
confidence: 99%